Perfecting Business Models in the Context of the Sources of Competitive Advantages - Michałowska , Mariola; Wiesław, Wiesław; Stankiewicz , Dariusz (Studia Oeconomica Posnaniensia, 2016)
The variability of the business environment causes change and improvement of the business model in the context of the sources of competitive advantage of the company and has become an important research field. Companies take action to improve their business model and implement development strategies appropriate to the changes emerging using their competitive potential which is a competitive advantage. This, based on the relevant means determines their competitive position. Nowadays having an appropriate action strategy, as well as the availability of innovative solutions and new technologies, is not an adequate key to success. Today a large guarantor of success is a properly constructed business model [Gwarda-Gruszczyńska 2012, p. 392]. This publication shows the elements of a business model, identifies factors affecting its form in conjunction with current and former sources of the competitive advantages of the company.